2018
DOI: 10.18203/2349-2902.isj20180842
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular agenesis: a case report

Abstract: Congenital agenesis or absence of vermiform appendix is very rare. Herein, author reported a case of a 28 years old Vietnamese lady who presented with a picture of acute appendicitis. During surgery, author failed to find the appendix. Postoperatively, she made uneventful recovery and she was diagnosed as a case of nonspecific abdominal pain (NSAP) with appendicular agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Embryologically, the vermiform appendix is formed around the 10 th week of pregnancy from the caecum as a tubular end-capped structure. Appendicular atresia known causes can be an intrauterine vascular accident or auto-amputations due to an intrauterine fibrous band [ 12 ]. Also, a developmental defect called the apple peel jejunal atresia (autosomal recessive transmission) and associated with short midgut syndrome can cause appendicular atresia.…”
Section: ⧉ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryologically, the vermiform appendix is formed around the 10 th week of pregnancy from the caecum as a tubular end-capped structure. Appendicular atresia known causes can be an intrauterine vascular accident or auto-amputations due to an intrauterine fibrous band [ 12 ]. Also, a developmental defect called the apple peel jejunal atresia (autosomal recessive transmission) and associated with short midgut syndrome can cause appendicular atresia.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Agenesis of the vermiform appendix may be isolated or may be part of a complex of ileo-cecal malformations. Collins studied this aspect and made the following classification: type I – absence of appendix and cecum; type II – rudimentary cecum and absence of appendix; type III – normal cecum and absence of appendix; type IV – normal cecum and rudimentary appendix; type V – giant cecum and absence of appendix [ 12 , 13 , 14 ]. The presented case is a type III.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Failure in the appendix development according to Hei et al, could be attributed to an intrauterine vascular accident, and in some cases is associated with intestinal atresia [12] , as well, toxic-associated with Thalidomide are described in literature as possible causes of appendix abnormalities [13] . Literature case reports of appendiceal absence are usually described in adult patients [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . There are no clinical manifestations of appendix agenesis, and usually are found in patients with acute abdomen suspicion that needs laparotomy, as in our case; following a systematic review of the cavity, no appendix were found.…”
Section: Discussionmentioning
confidence: 99%
“…First description of appendicular agenesis was made by Morgani et al [1] , incidence is approximately 1:100.000 laparotomies due to acute abdomen according to Chevre et al [2] , [3] . Non-specific causes of acute abdomen are usually due to acute appendicitis [2] , and diagnosis of appendicular agenesis are frequently performed in an incidental way [4] . Abnormalities of the appendix are unusual, and frequently there are not found because they do not show any signs or symptoms [2] , [3] , [4] .…”
Section: Introduction and Importancementioning
confidence: 99%
See 1 more Smart Citation